Peer group impulsivity moderated the individual-level relationship between depressive symptoms and adolescent nonsuicidal self-injury. (February 2016) - You, Jianing; Zheng, Chuhua; Lin, Min-Pei; Leung, Freedom
Abstract: This study examined the influence of impulsive friendship group contexts on nonsuicidal self-injury (NSSI) and how peer group impulsivity (i.e. negative urgency and premeditation) moderated the individual level relationship between depression and NSSI among 1701 Chinese secondary school students (1147 females). Participants were assessed twice over a 6-month interval. After controlling for direct socialization effects for NSSI, multilevel analysis indicated that friendship group negative urgency exerted a significant influence on NSSI. Additionally, friendship group premeditation weakened the relation between individual depression and NSSI, while friendship group negative urgency strengthened the relation between depression and NSSI. The results suggest the contribution of indirect peer influence effects to NSSI.